The Implementation of the ISMUBA Program at SMK Muhammadiyah 1 Palembang - Yulanda, Oddi; Zulkipli; Ade Akhmad Saputra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the implementation of the Al-Islam, Kemuhammadiyahan, and Arabic Language (ISMUBA) Program at SMK Muhammadiyah 1 Palembang and to identify the supporting and inhibiting factors affecting its implementation. The ISMUBA Program is a distinctive educational program of Muhammadiyah designed to develop students who are faithful, pious, morally upright, and knowledgeable about Muhammadiyah values, as well as possessing basic proficiency in Arabic. This research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation, involving the Vice Principal for ISMUBA Affairs as the key informant and teachers as supporting informants. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The findings indicate that the implementation of the ISMUBA Program at SMK Muhammadiyah 1 Palembang has been relatively effective, supported by religious habituation activities, classroom instruction, and school management support. The program has positively contributed to students’ learning outcomes and character development. Supporting factors include teacher competence, the availability of facilities and infrastructure, and a religious school environment. However, inhibiting factors include limited motivation, awareness, and enthusiasm among some students in participating in ISMUBA activities. Therefore, enhanced coordination, guidance, communication, and motivational strategies are necessary to optimize the implementation of the ISMUBA Program.